Novel Sensors for Food Inspection: Modelling, Fabrication and Experimentation - Abdul Rahman, Mohd Syaifudin (Smart Sensors, Measurement and Instrumentation, 2014)
This book addresses presents recent developments of novel planar interdigital sensors for food inspection. It covers the fundamentals of sensors, their design, modelling and simulations, fabrications, characterizations, experimental investigations and analyses. This book will be useful for the engineers and researchers especially higher undergraduate, postgraduate students as well as practitioners working on the development of Electromagnetic Sensors.